Factors Affecting Mortality in Rapidly Progressive Diabetic Foot Ulcer Patients - Demiröz, Anıl; Arslan, Hakan (Cerrahpaşa Medical Journal, 2019)
Objective: A diabetic foot ulcer with progressive infection is a life-threatening condition that requires urgent surgical intervention. Because of the severity of this condition, it is important to understand its epidemiological and prognostic background. This study aims to evaluate the epidemiology of the diabetic foot ulcer and describe the etiology and the surgical procedures performed to treat it. Methods: A retrospective review of 35 diabetic patients with foot ulcers was performed. These individuals were admitted to the emergency department and were subsequently hospitalized between April 2006 and April 2011. Factors affecting their mortality were statistically assessed. Results: The long duration of ulcer treatment and need for intensive care were found significantly related to mortality (p<0.05). There was a trend toward higher mortality in the patient group with cardiac comorbidity (24% versus 20%), but this was not found to be statistically significant. Conclusion: Infective diabetic foot ulcers may have a highly mortal course. Having knowledge of how to discriminate between the acute infection and the factors affecting patient mortality may lead us to making better prognoses and delivering more effective treatment. Cite this article as: Demiröz A, Arslan H. Factors Affecting Mortality in Rapidly Progressive Diabetic Foot Ulcer Patients. Cerrahpasa Med J 2019; 43(1): 23-28.